CEAA 2012: The End Of Federal EA As We Know It? - Doelle, Meinhard (Journal of Environmental Law and Practice, 2012)
This commentary assesses the key changes to the federal environmental assessment (EA) process contained in the 2012 Budget Implementation Bill. The resulting Canadian Environmental Assessment Act 2012 (CEAA 2012) is compared to the federal EA process that had been in place since the implementation of the original CEAA in 1995. The article concludes that the key changes brought about by the enactment of CEAA 2012, including the shift in responsibility for EA, the discretionary application of the process, the narrowed scope, new powers of delegation, substitution and equivalency, and the more restricted role of the public all function counter to the improvements to CEAA 1995 recommended in the academic literature. [PUBLICATION ABSTRACT]